An experimental study for carbonate reservoirs on the impact of CO2-EOR on petrophysics and oil recovery. (1st January 2019) - Khather, Mohamed; Saeedi, Ali; Myers, Matthew B.; Verrall, Michael
Abstract: The injection of CO2 into deep geological structures for the purpose of CO2 storage and/or enhanced oil recovery (CO2 -EOR) may trigger a series of consecutive chemical reactions (e.g. mineral dissolution and asphaltene precipitation) and physical effects (e.g. mechanical compaction and permeability variation). These reactions can significantly impact carbonate reservoirs, due to the presence of highly reactive minerals (e.g. dolomite and calcite), as well as the solvent/precipitation effects of supercritical CO2 on complex crude oil mixtures potentially containing heavy fractions such as wax and asphaltene. A core flooding study has been carried out to evaluate changes in the petrophysical properties of a number of heterogeneous carbonate samples (i.e. limestone and dolostone) after undergoing EOR activities under in situ reservoir conditions. In this study, a number of different measurement techniques are conducted to obtain a comprehensive view of the role that mineral dissolution, mechanical compaction and asphaltene precipitation plays during CO2 -EOR in carbonate reservoirs. The results show that CO2 injection results in higher oil recovery in all the samples evaluated as part of this study. However, early water breakthrough was observed for most samples suggesting a high degree of heterogeneity in the carbonate core samples. In all samples, a decrease in permeability was observed presumably due to asphaltene/resin precipitation and mineral dissolution/precipitation. Chemical analyses of the produced crude oil and scanning electron microscopy images confirmed the precipitation of asphaltene and mineral dissolution that caused permeability reduction. Furthermore, as CO2 concentration in the oil/CO2 mixture increased more asphaltene/resin precipitation was observed. More asphaltene precipitation was observed in higher permeability and more vuggy core samples than in those with intermediate or low permeabilities. This observation can be possibly attributed to relaxation of fluids as they enter the relatively large vugs (with large surface area) from the pore-throats resulting in the flocculation and/or precipitation of asphaltenes. A slight reduction in porosity and pore size was observed in most samples presumably caused by a combination of mineral/asphaltene precipitation and physical compaction. Overall, the results obtained in this study further highlight the complexities associated with the application of CO2 -EOR in underground oil reservoirs where both the crude oil and the rock formation may be expected to interact with the injected fluids. Further research into the underling mechanisms is required.